From ‘Imitation’ to ‘Indigenization’: A Study of Shakespeare Performances in Colonial Calcutta - Thakur, Vikram Singh (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2012)
The plays of William Shakespeare have been performed all over the globe. This is particularly true of the erstwhile colonies of Britain and India is no exception. Along with other English playwrights, Shakespeare’s plays began to be performed in India during the eighteenth century by British officials for their entertainment. Educated Indians took these performances as a model to develop ‘modern’ Indian theatre. The present essay engages with Shakespeare production in colonial Calcutta, starting with Shakespeare performances in English before moving on to consider the later process of ‘indigenizing’ Shakespeare. The essay also proposes that Shakespeare production in Calcutta after the 1850s when Shakespeare’s plays moved out of the confines of schools and colleges has been governed by its own aesthetics.